Enhancement of E-GSM Channel Capacity with Function Diversion of 3G to 2G Frequency - Achmad Ubaidillah Ms; Riza Alfita; Retno Diyah Pramana Sari (International Journal of Science, Engineering, and Information Technology, 2018)
The main observation of this reserch is the installation and analysis of frequency function diversion from 3G to 2G network to enhance the Channel capacity. The frequency 850 MHz that is previously owned by Telkom Flexi, then shifted to belong to Smartfren and will be transferred to become 2G GSM operated by Telkomsel Madura. The result shows that the transfer process of the frequency function goes well.  This produces that the average value of drive test before diversion are Rx Level = 87.969%, Rx Qual = 87.791%, SQI = 80.809%. The average value of drive test after diversion are Rx Level = 91.967%, Rx Qual = 89.926%, SQI = 82.049%. The traffic value before diversion is 503.296 Erlang and 627 Erlang for after diversion. While the blocking before diversion is 24.36% and the blocking after diversion is 1.6%.